Fast NMR Methods for Measuring in the Direct and/or Competition Mode the Dissociation Constants of Chemical Fragments Interacting with a Receptor. (14th May 2019) - Dalvit, Claudio; Parent, Annick; Vallée, Francois; Mathieu, Magali; Rak, Alexey
Abstract: Ligand‐based NMR screening represents a powerful method in fragment‐based drug discovery for the identification of chemical matter interacting with the receptor of interest. The large dynamic range of these methods allows the detection of weakly binding ligands. However, the methodology has not been extensively used for quantifying the strength of these interactions. This knowledge is important for ranking fragments according to their binding strength and for prioritizing structure‐based and medicinal chemistry activities. Rapid NMR methods for measuring the dissociation constant in direct and competition modes are presented here. The theory underpinning these methods are presented, along with their application to the measurement of the binding affinities of several ligands of the heat shock protein 90. Abstract : Fast affinity ranking : Rapid NMR spectroscopy methods for measuring dissociation constants in direct and competition modes are presented. The theory underpinning these methods is presented along with their application to the measurement of the binding affinities of several ligands of heat shock protein 90.